THE INFLUENCE OF INTERNAL AUDIT AND CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE OF COMPANIES IN JII (JAKARTA ISLAMIC INDEX) - Auliani; Nurlela; Wardhiah; Marzuki (PT. Radja Intercontinental Publishing, 2025)
This study aims to analyze the influence of internal audit and corporate governance on financial performance in companies in the JII (Jakarta Islamic Index). The data for this study were accessed by visiting the official website www.idx.co.id. The sampling technique in this study used purposive sampling and obtained 20 companies as samples from 30 companies in the JII (Jakarta Islamic Index) with a total of 100 observations. This study used the Multiple Linear Regression method using the IBM SPSS analysis tool. The results showed that Internal Audit had a negative and insignificant effect on financial performance, the Board of Commissioners had a positive and significant effect on financial performance, the Board of Directors had a positive and significant effect on financial performance.